An analysis of the debate between economic gobalization and regionalization based on Rawls’s theory of justice - Chiang, Hsin-yen; Ting, Jen-fang (School of History, Politics and Strategic Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Driven by globalization, international economic integration has become unavoidable. Within this broader trend, two distinctive modes of international regime building can be identified globalism and regionalism. Globalism, illustrated using the case of the World Trade Organization (WTO), pushes forward global economic integration using established norms. In contrast, regionalism involves gradual expansion of regional integration mechanisms based on interests of member states. This study assesses these two development modes with justice as a concept of moral rightness. To this effect, Rawls’s theory of justice is applied to evaluate standards of justice in international regimes. Based on Rawls’s two principles of justice, three assessment criteria are developed: (1) equal qualification principle, (2) equal opportunity principle, and (3) difference principle. These criteria are applied for comparative analysis of justice in the development of global and regional regimes in order to develop a model for international regimes that is consistent with the concept of justice. A comparison of (1) qualifications for membership; (2) fairness of decision making mechanisms, and (3) institutionalization of differential treatment shows that justice in global regimes is superior to that in regional regimes. In other words, in terms of the philosophy of moral rightness, states should pursue integration based on the principles of globalism.